Urgensi Kepemimpinan Transformasional Perkembangan Budaya Belajar Di Sekolah - Annisa Ayuning Tyas; Latifatum Muthoharoh; Lutfi Zainatul Muslihah; Umi Luthfiyatul; Tamrin Fathoni (Tamilis Synex: Multidimensional Collaboration, 2024)
Developing a quality culture in educational institutions can be achieved by developing educational innovations, extracurricular activities, cultural activities, student character development, and programs to develop academic and non-academic achievement. This study aims to determine the urgency of transformational leadership in schools. Implementing transformational leadership principles in schools can provide important lessons for students and teachers because this leadership fosters innovation and provides motivation focused on quality targets and follow-up. Furthermore, this paper will describe the impact of transformational leadership on the development of innovation and culture in leadership education.